Clinical researchPatients with diabetes mellitus with ischemic stroke have a higher hemoglobin A1c level and a higher serum low-density lipoprotein cholesterol level than diabetics without ischemic stroke - Ravipati, Gautham; Aronow, Wilbert; Kumbar, Sujata; Kumar, Anil; Rapera-Lleva, Ranee; Menga, Gwendoline; Weiss, Melvin B.; McClung, John A. (Archives of Medical Science, 2009)
Introduction: To investigate the association between the hemoglobin A1c level and the serum low-density lipoprotein (LDL) level in diabetics with and without ischemic stroke. Material and methods: The patient population included 408 diabetics, mean age 66 years, with ischemic stroke and 404 age-matched and gender matched diabetics without ischemic stroke. The prevalence of race, hypertension, use of statins, current smoking, obesity, carotid arterial disease, obstructive coronary artery disease, prosthetic valve, and atrial fibrillation was not significantly different between diabetics with and without ischemic stroke. Results: The hemoglobin A1c level was < 7.0% in 141 of 408 diabetics (35%) with stroke and in 221 of 404 diabetics (55%) without stroke (p < 0.001). The serum low-density lipoprotein (LDL) cholesterol was < 100 mg/dl in 164 of 408 diabetics (40%) with stroke and in 269 of 404 diabetics (67%) without stroke (p < 0.001). The serum LDL cholesterol was < 70 mg/dl in 34 of 408 diabetics (8%) with stroke and in 127 of 404 diabetics (31%) without stroke (p < 0.001). Conclusions: Diabetics should have their hemoglobin A1c level reduced to < 7.0% and their serum LDL cholesterol reduced to < 70 mg/dl.